Cash conversion cycle and profitability: a case study of selected listed manufacturing companies in sri lanka - Rathika, S.; Nimalathasan, B. (University of Jaffna, 2012)
The present study provides cash conversion cycle (CCC) and profitability of selected listed manufacturing companies during the period from financial year 2006 to 2010. In order to select the sample, convenience sampling technique was used. Further the study suitably used secondary data. Correlation and regression analysis were performed. Results revealed that CCC and profitability (i.e., Return on Assets (ROA)) are negatively correlated with the value of -0.663 which is highly significant at five percent level. A result of the regression analysis is CCC is 0.439 which means 43.9 percent impact on profitability. This study would hopefully benefit to the academicians, researchers, policy makers and practitioners of Sri Lankan and other similar countries through exploring the impact of CCC and on profitability and pursuing policy to improve the current status of it.
Keywords: Cash Conversion Cycle; Manufacturing Companies; Profitability